Keanekaragaman dan Kemelimpahan Jenis Tumbuhan Invasif di Hutan Wisata Penggaron Kabupaten Semarang Jawa Tengah - Utami, Sri; Murningsih, M (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Forests are ecosystems that have very potential natural resources, including storing high genetic resources. One of the things that threatens the decline of genetic resources in the forest is the presence of invasive species. This study aims to determine the species of invasive plants and their abundance in the Penggaron tourism forest of Ungaran Regency, Central Java. The research method was carried out by exploring the entire forest area through the path. The results of the study showed that 13 species of invasive plants were included in 7 families. The most number of invasive plants from the Poaceae family include 5 species : Axonopus Compressus, Cynodon dactylon, Pennisetum purpureum, Paspalum conjugatum and Eleusine indica. The highest relative abundance was Eleusine indica and was followed by Synedrella nodiflora, Elephantopus scaber and Paspalum conjugatum. The species of invasive plants, especially the abundant ones, need to be controlled by the population so as not to threaten native plants and cause environmental degradation in Penggaron tourism forests.Â Key word : Invansive plant, Penggaron tourism forest, genetic resources.